Los alumnos prefieren diferentes estrategias didácticas de la enseñanza de las ciencias en función de sus características motivacionales - Martín Díaz, M. J.; Kempa, R. F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
We carried out empirical research into the relationship between students' motivational patterns and their preferences for different teaching procedures in science education. According to the results obtained, students tend to prefer those teaching procedures and strategies that allow their motivational needs to be met and reject those conflicting with them.